Been there before? Examining “familiarity” as a moderator for discriminating between true and false intentions - Knieps, Melanie; Granhag, Pär A.; Vrij, Aldert (Frontiers in Psychology, 2014)
Prospection is thinking about possible future states of the world. This capacity allows people to better foresee, plan, and shape their futures. Commitment to perform a future action - commonly referred to as intention - is a specific type of prospection. An important observation is that thinking of, and committing to, future actions often evoke vivid and detailed mental images. These simulations are affected by how familiar a person is with the location of the future event. Research on prospection has recently become of interest in deception research related to future actions. The purpose of this study was to examine to what extent location-familiarity moderates how liars and truth tellers describe a mental image in an investigative interview. Liars were instructed to plan a criminal act and truth tellers were instructed to plan a non-criminal act. Before they could carry out these acts, the participants were intercepted and interviewed about the mental images they may have had experienced in this planning phase. Truth tellers told the truth whereas liars used a cover story to mask their criminal intentions. As predicted, the results showed that the truth tellers reported a mental image significantly more often than the liars. If a mental image was reported, the content of the descriptions did not differ between liars and truth tellers. In a post interview questionnaire, the participants rated the vividness (i.e., content and clarity) of their mental images. The ratings revealed that the truth tellers had experienced their mental images more vividly during the planning phase than the liars. In conclusion, this study indicates that both prototypical and specific representations play a role in prospection. However, the data did not support our assumption that location-familiarity is a moderator for discriminating between true and false intentions. How these findings can be helpful for detecting deception related to future actions will be discussed.